Effect of Hot Spot Temperature to The Temperature and Current Distribution in Transformer-Oil Based Nanofluids - Azzam, A. F. R.; Othman, N. A.; Rahman, R. A.; Kamarden, H. (Evolution in Electrical and Electronic Engineering, 2020)
Heat transfer coefficient must be in adequate level to ensure the transformer oil is in good condition. The presence of power losses in the core and windings in the form of heat may cause the transformer oil to deteriorate easily. Continuous monitoring of transformer heat distribution could provide useful information on the hot spot temperature (HST) development. Therefore, this paper simulates a 30MVA Oil Natural Air Natural (ONAN) transformer temperature distribution pattern with and without HST. This study aims to observe the effect of three different HST values located at the top of HV winding on the temperature distribution. Next, the correlation between temperature and current distribution with the presence of HST was also included. Mineral oil and transformer oil-based Al2O3 nanofluid was used in this study to determine transformer oil with better heat transfer coefficient in convection process. Results show that the presence of HST causes an increased in temperature distribution at the top of the transformer. It is also evident that the usage of transformer oil-based Al2O3 nanofluid improves overall heat transfer characteristics of the base fluid. Also, it is found that the temperature and current distribution pattern was similar that indicates a correlation between both parameters.